DEGRADATION OF AQUEOUS 1-BUTYL-3-METHYLIMIDAZOLIUM CHLORIDE USING FENTON’S OXIDATION: THE OPTIMIZATION STUDY - MUHAMMAD ALI, MOHAMED AMIN (IRC, 2017)
Although ionic liquids (ILs) have been characterized as an eco-friendly solvent due to its low vapor pressure, its high stability and solubility causing them to accumulate in water stream. The wastewater contaminated with ILs would inflict a potential danger to the aquatic organism. This is because the wastewater polluted by organic solvents is characterized with high chemical oxygen demand (COD). Due to the high COD value, it is not possible to treat the wastewater using the conventional wastewater treatment system. The purpose of this research is to study on the degradation mechanism of ILs using Fenton’s oxidation system. The ionic liquid chosen for this research purpose is 1-Butyl-3-Methylimidazolium chloride which is also known shortly as [Bmim]Cl. According to the previous research done, the degradation would result in the reduction of COD content within the ILs solvent. From the research, by utilizing the Fenton’s oxidation system as a treatment alternative, it had effectively degraded many types of ILs such as imidazolium, pyridinium, ammonium and phosphonium, in water stream. In order to treat the ILs, mixtures of H2O2 and Fe2+ known as the Fenton’s reagent will be used to oxidize the simulated wastewater containing [Bmim]Cl. By adhering to certain parameters according to the research papers, the degradation of the [Bmim]Cl was completed within 10 minutes. From the experiment, the optimum parameter for the degradation of [Bmim]Cl are predicted using the Design Expert software. The optimum initial concentration of [Bmim]Cl, concentration of hydrogen peroxide (H2O2), concentration of ferrous ion and pH, were 2000 mg/L, 0.4 mol/L, 0.04 mol/L and 4, respectively. Based on the Response Surface Methodology (RSM) result, a linear model equation was obtained. Moreover, it was found that only initial concentration of [Bmim]Cl, concentration of H2O and concentration of ferrous ion have significant effect on the degradation efficiency of [Bmim]Cl.